Formulação e formação de estratégias : análise nos segmentos atacadista, varejista e processador da cadeia de confecções e vestuário da região de Londrina, PR - Nonaka, Henry Tetsuji (2007)
In this work the results of a research done in fifteen micro and small cloth manufacturing companies in Londrina town are presented, aiming to identify the process of strategy formulation and formation, having as bases the classification model defined by Mintzberg (1973) and the strategy orientation model defined by Idenburg (1993). It was intended to identify specific points in these organizations. The micro and small companies studied were selected in an intentional way by judging. The groups of cloth manufacturing companies interviewed could be divided in wholesalers, retailers and processers. The data collecting happened through the realization of interviews with the owners/managers. It was noticed that, according to the aspects of the strategist profile model, the most present are the enterpreuneship and the adaptative, the planners were not found among the interviewed ones. According to the Idenburg (1993) model, the most present orientations were the logical incrementalism, learning and emergent and in this model the planning orientation was not expressive too. From that was possible to understand specific and particular points of the intervewed ones related to each model as described in literature.